1981
DOI: 10.1073/pnas.78.11.6613
|View full text |Cite
|
Sign up to set email alerts
|

Use of synthetic oligonucleotides as hybridization probes: isolation of cloned cDNA sequences for human beta 2-microglobulin.

Abstract: We have synthesized two sets of 15-base-long oligodeoxyribonucleotides corresponding to all possible coding sequences for a small portion of human fl2-microglobulin. Labeled oligonucleotides were used as hybridization probes to screen bacterial clones containing cDNA sequences primed with oligo(dT) and inserted into the plasmid vector pBR322. One A-microglobulin cDNA clone was detected in the 535 bacterial plasmid clones that were screened. The clone has been characterized by blotting and nucleotide sequence a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
152
0

Year Published

1984
1984
2004
2004

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 372 publications
(155 citation statements)
references
References 36 publications
3
152
0
Order By: Relevance
“…The degradation process of β2-m is based on heat liability and pH sensitivity microglobulins from different species. The data for the dog protein were from Smithies and Poulik [23]; for the human protein are from Suggus et al [24]; for the mouse protein from Gates et al [6]; for the rabbit protein from Gates et al [5]. A solid line indicated identity with the purified protein sequence.…”
Section: Discussionmentioning
confidence: 99%
“…The degradation process of β2-m is based on heat liability and pH sensitivity microglobulins from different species. The data for the dog protein were from Smithies and Poulik [23]; for the human protein are from Suggus et al [24]; for the mouse protein from Gates et al [6]; for the rabbit protein from Gates et al [5]. A solid line indicated identity with the purified protein sequence.…”
Section: Discussionmentioning
confidence: 99%
“…Additional validity control was achieved by a Southern blot analysis of the PCR product using an internal oligonucleotide probe as previously described (Roberts et al, 1997) (data not shown). Amplification of an endogenous marker, the human b 2 -microglobulin cDNA, was used as an internal control, because its related protein is found on the surface of many nucleated cells (Suggs et al, 1981).…”
Section: Rt-pcr Analysismentioning
confidence: 99%
“…VD treatment is crucial for VDR detection, since nuclear extracts obtained from untreated cells do not contain VDR detectable by Western blot analysis (data not shown and Figure 2A, allow two main observations: (a) a wide variability in VDR levels exists among the cell lines studied, in particular K562 and KG-1a appear to contain very little VDR; (b) the apparent molecular weight of VDR is not homogeneous in different cell types. Since it is known that VDR is a phosphoprotein (Brown and DeLuca, 1990;Suggs et al, 1992), we have investigated whether phosphorylation might be the basis for this size variability. Indeed, calf intestinal alkaline phosphatase (CIAP) treatment of KG-1 nuclear extracts leads to the detection of a VDR band ( Figure 2B, lane 10) which is approximately 1 Kd smaller than in the untreated nuclear extract (lane 9).…”
Section: Vdr Expression and Phosphorylationmentioning
confidence: 99%
“…10 ml of each sample was then electrophoresed on a 2% agarose gel. RT ± PCR analysis was performed using oligodeoxy-nucleotide primers specific for CD14 antigen (Ferrero and Goyert, 1988), HMSE-1 (Zschunke et al, 1991), p21 waf-1 (el Deiry et al, 1993), human osteocalcin (hOC) (Kiefer et al, 1990) and b2 microglobulin (b2m) (Suggs et al, 1992). The oligonucleotides used as direct primer (DP) or reverse primer (RP) were: CD14-DP, 5'-TCCAGAGCCTG-TCCGGAGCTCAGA-3'; CD14-RP, 5'-GCGTTCGCCCAGTCCAGGATTGTCA-3'; HMSE1-DP, 5'-CCTCCTATGTGCACCCAAGAT-3'; HMSE1-RP, 5'-GCATCCCAT-CAATCACAGTGC-3'; p21 waf-1 -DP, 5'-AGTTCCTTGTGGAGCCG-GAGCTGGG-3'; p21 w a f -1 -RP, 5'-TCCAGGACTGCAGGCTT-CCTGTGGG-3'; hOC-DP, 5'-GAGCCCTCACAC-TCCTCGCCCTATT-3'; hOC-RP, 5'-GTAGAAGCGCCGATAGGCCTCCTGA-3'; b2m-DP, 5'-CTCGCGCTACTCTCTCTTTCT-3'; b2m-RP, 5'-TCCATTCTTCAG-TAAGTCAACT-3'.…”
Section: Rna Analysismentioning
confidence: 99%